The Impact of Tabarru Contracts and Income on Customers' Decision to Choose Life Insurance at AIA Sharia Unit - Dirmawati, Dirmawati; Jannah, Raodahtul; Sabir, Sadli; Irwan, Irwan (PT FORMOSA CENDEKIA GLOBAL, 2024)
This study aims to investigate the effect of tabarru contracts and income on customer decisions in choosing life insurance in AIA sharia units. The research method used is quantitative with a descriptive approach. Primary data was collected through the distribution of questionnaires, observation, and documentation, using simple random sampling techniques. The research sample consisted of 50 respondents, and data analysis was carried out using multiple linear regression and using the SPSS version 20 application. The results showed that, partially, the tabarru contract had a positive and significant influence on customer decisions in choosing life insurance at the AIA sharia unit.